Pseudogap in cuprates driven by d-wave flux-phase order proximity effects: A theoretical analysis from Raman and ARPES experiments - Bejas, Matias Hector (2014)
One of the puzzling characteristics of the pseudogap phase of high-Tc cuprates is the nodal-antinodal dichotomy. While the nodal quasiparticles have a Fermi liquid behaviour, the antinodal ones show non-Fermi liquid features and an associated pseudogap. Angle-resolved photoemission spectroscopy and electronic Raman scattering are two valuable tools which have shown universal features which are rather material-independent, and presumably intrinsic to the pseudogap phase. The doping and temperature dependence of the Fermi arcs and the pseudogap observed by photoemission near the antinode correlates with the non-Fermi liquid behaviour observed by Raman for the B1g mode. On the other hand, similar to the nodal quasiparticles detected by photoemission, the Raman B2g mode shows Fermi liquid features. We show that these two experiments can be discussed, in the context of the t-J model, by self-energy effects in the proximity to a d-wave flux-phase order instability. This approach supports a crossover origin for the pseudogap, and a scenario of two competing phases. The B2g mode shows in underdoped a depletion at intermediate energy which has gained a renewed interest. We study this depletion and discuss its origin and relation with the pseudogap.